1995
DOI: 10.1111/j.1365-2133.1995.tb06920.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopa reaction of fetal melanocytes before and after skin transplantation on to nude mice

Abstract: We have previously demonstrated that human fetal epidermal melanocytes are dopa-negative. The present study was conducted to test the hypothesis that human fetal melanocytes can be activated to produce melanin under conditions differing from their natural in utero environment. To address this question, dopa staining activity of fetal epidermal sheets, obtained from seven aborted fetuses with estimated gestational ages of 13-20 weeks, was evaluated before and after engraftment on to nude mice. Dopa staining bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…This study confirmed an association of AA with NKG2D‐activating MICA family members, most notably ULBP3, and overexpression of NKG2D ligands in patients with AA . Shortly thereafter, the first functional proof for the importance of IFNg‐secreting NKG2D + cells in AA pathogenesis was provided by a new humanized mouse model of AA .…”
Section: Viewpointsupporting
confidence: 70%
“…This study confirmed an association of AA with NKG2D‐activating MICA family members, most notably ULBP3, and overexpression of NKG2D ligands in patients with AA . Shortly thereafter, the first functional proof for the importance of IFNg‐secreting NKG2D + cells in AA pathogenesis was provided by a new humanized mouse model of AA .…”
Section: Viewpointsupporting
confidence: 70%
“…3B). Furthermore, DOPA staining, as a morphological indicator of tyrosinase activity [25], confirmed the decreased tyrosinase activity following CoQ 10 treatment (Fig. 3C).…”
Section: Resultsmentioning
confidence: 70%
“…Interestingly, we have previously found that there is an expansion of NKG2A+ NK cells within psoriatic skin (20). An important role for NK cell receptors in cutaneous autoimmune disease is also observed in studies of alopecia areata, in which the interaction of the activating NK receptor NKG2D with its ligands MICA and ULBP3 leads to immune attack of the hair follicle (21)(22)(23).…”
Section: Discussionmentioning
confidence: 83%